Death Don’t Have No Mercy and Neither Does Calcium:Arabidopsis cyclic nucleotide gated channel2 and Innate Immunity - Ali, Rashid; Ma, Wei; Lemtiri-Chlieh, Fouad; Leng, Qiang; Bodman, Susannne von; Berkowitz, Gerald A.; Tsaltas, Dimitrios (My University, 2007)
Plant innate immune response to pathogen infection includes an elegant signaling pathway leading to reactive oxygen species generation and resulting hypersensitive response (HR); localized programmed cell death in tissue surrounding the initial infection site limits pathogen spread. A veritable symphony of cytosolic signaling molecules (including Ca2+, nitric oxide [NO], cyclic nucleotides, and calmodulin) have been suggested as early components of HR signaling. However, specific interactions among these cytosolic secondary messengers and their roles in the signal cascade are still unclear. Here, we report some aspects of how plants translate perception of a pathogen into a signal cascade leading to an innate immune response. We show that Arabidopsis thaliana CYCLIC NUCLEOTIDE GATED CHANNEL2 (CNGC2/DND1) conducts Ca2+ into cells and provide a model linking this Ca2+ current to downstream NO production. NO is a critical signaling molecule invoking plant innate immune response to pathogens. Plants without functional CNGC2 lack this cell membrane Ca2+ current and do not display HR; providing the mutant with NO complements this phenotype. The bacterial pathogen–associated molecular pattern elicitor lipopolysaccharide activates a CNGC Ca2+ current, which may be linked to NO generation due to buildup of cytosolic Ca2+/calmodulin.
Keywords: Nucleotides, Cyclic; Cyclic Nucleotide-Gated Cation Channels; Guanylate Cyclase